Husband’s Support and Mothers’ Attitudes in Choosing Long-Acting Reversible Contraceptives (LARCs) Postpartum: A Correlational Study - Kustin (Journal of Nursing Periodic, 2026)
Background: Long-Term Contraceptive Methods (MKJP) are an effective and useful contraceptive option to support family planning (KB) programs, especially during the postpartum period. However, maternal willingness to use MKJP after delivery remains low. This does not indicate a negative attitude toward MKJP; rather, it is influenced by many factors, one of which is a lack of husband support. Objective: The purpose of this study was to determine the relationship between husband support and maternal attitudes toward MKJP contraceptive use in the postpartum ward of Bhayangkara Bondowoso Hospital. Method: The study was designed using a correlative analytical cross-sectional design. Quantitative methods were used. The study population consisted of all postpartum mothers in the postpartum ward of Bhayangkara Bondowoso Hospital, with 40 mothers giving birth during the study period. The measurement instrument used a questionnaire that had been tested for validity and reliability. Data analysis was conducted using bivariate analysis with selected statistical tests using SPSS with the Spearman test. Results: The results showed that 30 respondents (75%) received support from their husbands, most of whom were positive, namely 23 respondents (57.5%). Furthermore, out of 10 respondents (25%) who did not receive support from their husbands, most of the mothers had a negative attitude, namely 8 respondents (20%). The test results obtained a sig. (2-tailed) value of 0.001, which means that there is a strong relationship between husband's support and the mother's attitude in choosing contraception, namely p-value <0.05. Discussion: Husbands are expected to play an active role in supporting their wives in using MKJP after delivery. This support can be demonstrated through involvement in family planning counseling, providing emotional support, respecting their wives' decisions, and increasing their knowledge regarding the benefits and safety of MKJP.